Helicobacter pylori Mutations Conferring Resistance to Fluoroquinolones and Clarithromycin among Dyspeptic Patients Attending a Tertiary Hospital, Tanzania - Hyasinta Jaka; Nele Rüttgerodt; Wolfgang Bohne; Andreas Mueller; Uwe Gross; Christa Kasang; Stephen E. Mshana (Canadian Journal of Gastroenterology and Hepatology)
Objectives. Helicobacter pylori (H. pylori) isolates resistant to clarithromycin and quinolones are increasing worldwide. Data regarding the magnitude of H. pylori resistance are limited in developing countries. Here, we report the prevalence of mutations conferring resistance to clarithromycin and fluoroquinolones among dyspeptic patients attending a tertiary hospital, Tanzania. Methods. Between August 2014 and August 2016, patients undergoing upper gastrointestinal endoscopy at the Bugando Medical Centre were enrolled. Biopsies were taken for polymerase chain reaction (PCR) and sequencing to detect mutations conferring resistance to clarithromycin and fluoroquinolones. Results. A total of 208 nonrepetitive biopsies were examined of which 188 (90.4%) tested positive for H. pylori specific 23S rRNA PCR. Clarithromycin resistance mutations were detected in 54/188 (28.7%) of patients tested. The most frequently detected mutation was A2143G (30) followed by A2142G (20). Out of 131 nonrepetitive biopsies tested for fluoroquinolones resistance mutations, 77/131 (58.8%) were positive, with N87I (20) mutation being the most frequently detected mutation followed by A92T mutation which was detected in 16 samples. Conclusion. A significant proportion of dyspeptic patients attending tertiary hospital in Tanzania are infected with H. pylori strains harbouring clarithromycin or fluoroquinolones resistance mutations. Detection of more than 50% of strains with fluoroquinolones resistance mutations makes the H. pylori second line treatment questionable in our setting. There is a need of surveillance of H. pylori resistance patterns in Tanzania to provide data that can guide empirical treatment to reduce associated morbidity of H. pylori infections. The correlation between A92T fluoroquinolone mutation and phenotypic resistance requires further investigations.